Enhancing mathematical education with spatial visualization tools - Medina Herrera, Linda Margarita; Juárez Ordóñez, Saúl; Ruiz-Loza, Sergio (Frontiers in Education, 2024)
This article highlights the innovative approach of incorporating spatial visualization tools in mathematics education, specifically focusing on the exploration of virtual environments and 3D printing. By integrating these advanced technologies, educators can enhance the learning experience and facilitate a deeper understanding of mathematical concepts. This research delves into the potential benefits and practical applications of these tools, shedding light on their effectiveness in fostering spatial reasoning skills and promoting active student engagement. The study aims to uncover new avenues for leveraging technology in the mathematics classroom and re-imagining the teaching and learning process. To assess the progress in spatial visualization ability, the Revised Purdue Spatial Visualization Test (Revised PSVT: R) was administered as both a pre-test and a posttest to a sample of 255 students divided into control and experimental groups. The findings indicate that the control group exhibited no significant development (p=0.163) and had a minimal effect size of change (g=0.035), whereas the experimental group demonstrated a substantial improvement in spatial visualization ability (p <0.05) with a noteworthy medium effect size of change (g=0.325). Furthermore, an analysis of variance was conducted to compare the mean normalized change in spatial visualization ability between the control and experimental groups. The results, with 95% confidence, establish that the normalized spatial visualization change is significantly higher in the experimental group. Specifically, the experimental group witnessed a 25% increase in spatial visualization skills, while the control group only experienced a 5% increase. Our study demonstrates the significance and effectiveness of integrating spatial visualization tools in mathematics education to enhance students' spatial reasoning skills and mathematics understanding.